ANALISIS GANGGUAN DAN IDENTIFIKASI KABEL FIBER OPTIC MENGGUNAKAN OTDR DI OTB CIREBON-BREBES R4 - Mohammad Khrisna Nurwijaya (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Fiber optic cables that experience interference and breaks are a common problem in modern communications infrastructure. Interference and breaks in optical cables can disrupt data transmission between locations and cause a decrease in signal quality. The use of an Optical Time Domain Reflectometer (OTDR) has become a common method for detecting faults in optical cables by displaying the attenuation of the cable under test. Although optical fiber has a large capacity and high speed for transmitting information, relatively small attenuation still has a significant impact on transmission quality. The importance of maintaining and handling this interference is because attenuation can cause power loss in fiber optic transmission, hamper data transmission, and affect the quality of internet services